Multiple target detection and tracking with guaranteed framerates on mobile phones - Wagner, Daniel; Schmalstieg, Dieter; Bischof, Horst (2009 8th IEEE International Symposium on Mixed and Augmented Reality, 2009)
In this paper we present a novel method for real-time pose estimation and tracking on low-end devices such as mobile phones. The presented system can track multiple known targets in real-time and simultaneously detect new targets for tracking. We present a method to automatically and dynamically balance the quality of detection and tracking to adapt to a variable time budget and ensure a constant frame rate. Results from real data of a mobile phone Augmented Reality system demonstrate the efficiency and robustness of the described approach. The system can track 6 planar targets on a mobile phone simultaneously at framerates of 23fps.